The Use of Propolis in Micro/Nanostructured Pharmaceutical Formulations - L. Bruschi, Marcos; R. de A. Pereira, Raphaela; M.B. de Francisco, Lizziane (Recent Patents on Drug Delivery & Formulation, 2016)
Background: Propolis is a resinous material with complex chemical structure, produced by bees using plant sources, displaying a wide spectrum of biological activities. Methods: Many studies have reported the use of this compound in pharmaceutical, medicinal, veterinary and dentistry areas, and the results have reported its pharmacological activities. Results: Moreover, many propolis delivery systems have been proposed and evaluated, indicating that they can be used. On the other hand, considering its chemical and physical characteristics, propolis could be used as a material to produce micro/nano-structured pharmaceutical formulations. Conclusion: This work reviews the recent studies of development of micro/nanostructured systems using propolis or its byproduct. In addition, patents were reviewed and categorized.
Keywords: patents